THE INFLUENCE OF ORGANIZATIONAL CULTURE ON ORGANIZATIONAL PREFERENCES TOWARDS THE CHOICE OF ORGANIZATIONAL CHANGE STRATEGY - Janićijević, Nebojša (Economic Annals, 2012)
Organizational culture, through its assumptions, values, norms and symbols, determines the way in which the members of an organization perceive and interpret the reality within and around their organization, as well as the way they behave in that reality. For this reason we may assume that organizational culture has an impact on the way in which an organization changes, and that matching of organizational culture and change strategy will improve the efficiency of the change process. In this paper specific hypotheses about the causal relationship between certain types of organizational culture and certain change strategies are formulated. Types of organizational culture are differentiated according to Handy’s and Trompenaars’ classifications. Organizational change strategies have been differentiated according to previous work of Chin & Benne but one more strategy has been added. Classifications of both the organizational cultures and of the organizational change strategies are based on the same criteria of differentiation: distribution of power in an organization and orientation toward relationships or tasks. For this reason it is possible to formulate hypotheses about the causal relationship between certain types of organizational cultures and certain types of organizational change strategies. Thus, eight hypotheses are formulated in this paper, relating particular change strategies with particular types of organizational culture.